Review of Cultural Studies; The Main Character from Murakamiâs Novel Shikisai wo Motanai Tsukuru Tazaki - Isnaini, Zuli Laili; Budiani, Dini; Aulia, Noni (Proceedings of the UR International Conference on Educational Sciences, 2018)
Cultural studies explores not only various concepts of cultures, tagging, representation, pop cultural, but also ideology, hegemony, text, active audience, subjectivity, discuss issues of subjectivity, identity, ethnicity, and subcultural. This article shows that ijime is a process for Japanese teenagers to became survive for their struggle and pain. Tsukuru is a main character in Murakamiâs novel stumbling into her meaningless existence as a human and social community. The social construction of the "uchi and sotoâin community system of Japan are not able to eradicate ijime, more ever practice of ijime is thought to be a processes of independence or maturity for a person.